2014
DOI: 10.1111/sji.12155
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of an Oral Somatostatin DNA Vaccine without Antibiotic Resistance Gene in Promoting Growth of Piglets

Abstract: This study aimed to evaluate the efficacy and safety of an oral DNA vaccine against somatostatin (SS) (pGS/2SS‐asd, encoding two copies of somatostatin genes) mediated by attenuated Salmonella choleraesuis C500 without antibiotic resistance gene on piglets growth. A total of 50 piglets were uniformly divided into five groups. The animals in the first three groups were orally given vaccine in dose of either 5 × 1010, 5 × 109 or 5 × 108 colony‐forming units (CFU). The remaining two groups were orally administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Although the previous studies have reported various somatostatin genetic vaccines including naked pCS/2SS plasmid and pVGS/2SS plasmid delivered by attenuated Salmonella , the growth-promoting effect of DNA immunization is still unsatisfied [ 7 , 11 ]. Cortistatin (CST) is a neuropeptide that shares high structural and functional homology with somatostatin and has a compensatory effect with somatostatin as found in single SS knockout mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the previous studies have reported various somatostatin genetic vaccines including naked pCS/2SS plasmid and pVGS/2SS plasmid delivered by attenuated Salmonella , the growth-promoting effect of DNA immunization is still unsatisfied [ 7 , 11 ]. Cortistatin (CST) is a neuropeptide that shares high structural and functional homology with somatostatin and has a compensatory effect with somatostatin as found in single SS knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin (SS) consists of 14 peptides and is a pleiotropic neuropeptide widely distributed throughout the organism, which is generally viewed as a crucial regulator of several hormones, including growth hormone (GH) [ 1 , 2 ], prolactin (PRL) [ 3 ], follicular stimulating hormone (FSH) [ 4 ], and luteinizing hormone (LH) [ 5 ]. Cumulative studies have demonstrated that both active and passive immunization against somatostatin (SS) could induce a rise in growth hormone, thereby improving the growth or lactation performance of animals such as mice [ 6 , 7 ], chickens [ 8 ], Hu lambs [ 9 ], goats [ 10 ], and piglets [ 11 ]. However, the growth-promoting effect of animals is still not satisfying, especially for large animals.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the dose of vaccine may also be a significant contributor to this phenomenon. Han et al reported that oral administration of a 5 × 10 10 CFU/mL concentration of SS DNA vaccine induced 100% antibody positivity in piglets, while 5 × 10 9 CFU/mL and 5 × 10 8 CFU/mL concentrations induced 30% and 20% antibody positivity, respectively [ 20 ]. Furthermore, we examined the levels of cytokines in the serum, and the results showed that the concentrations of IL-4 and IFN-γ in the P group were not significantly different from those in the N group.…”
Section: Discussionmentioning
confidence: 99%
“…Immunisation against SS has been reported to enhance growth in various species, including mice [ 31 ], lambs [ 9 ], rats [ 22 ], and cattle [ 8 ]. Previous studies in the laboratory have reported that the SS DNA vaccine is attributable to improving the growth performance of piglets through an influence on GH secretion [ 20 ]. In this study, we evaluated the effect of the SS DNA vaccine on growth promotion in fattening pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation